Teknologi Tepat Guna pada Induk Kambing Melalui Penerapan Breeding Center Dan Flushing di Sentra Peternakan Rakyat Kebon Wulangreh, Desa Karangdukuh, Klaten - Bayu Andri Atmoko; I Gede Suparta Budisatria; Nono Ngadiyono; Febri Aryanti; Panjono Panjono (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2018)
Goat farms in Karangdukuh are still traditionally maintained in the yard of the house and grazed in the fields. The scale of ownership and the spread of the farm location make estrous detection so difficult, the absence of superior buck leads to a genetic quality degradation. The concept of breeding center is the provision of superior buck and mating house in one location. To support the increase of the does performance need for improvement of feed during in the breeding center, namely flushing. The partners of community engagement are farmers at Sentra Peternak Rakyat Kebon Wulangreh in Karangdukuh, Jogonalan, Klaten. It was done from April to October 2017. Activities began with socialization, followed by community learning and then was done the empowerment of farmers for built a breeding center was consisting of mating house, pasture, arteis well and electrical installation. The breeding center concept was applied after complete. Breeding center is a simple solution for estrous detecting and limitation of superior buck, more controlled does health, improvement for genetic quality and performance, so that kids crop can be increases and finally impact on the farmer prosperity. Enggagement activities already done on target and get very postive responses. Farmers have doing together to build a breeding center area and have been used. They are able to make flushing and will be continued independently.